Basic Conditions of Performing Freedom in Teaching Methods by F. Liszt and N. K. Medtner in the Aspect of Romantic View of the World - Kuznetsova, Alina; Kurganskaya, Olga; Kurganskiy, Sergey; Kaishaury, Etery (Journal of History Culture and Art Research, 2018)
Ideas on the relationship between the notes of the gamma scale were perceived from the time of antiquity to the Enlightenment as a key to understanding the structure of the universe with a characteristic analytic component. Disclosure emphasis of the human in culture determined the higher ideals associated with the self-knowledge of man, with the overcoming of the constraining conventions of being. The change in the musical form of the work in the era of Romanticism is largely due to the invention of the modern setting, known as a uniform temperament, the acceptance of it was made hard primarily by mathematical and philosophical discourse over the centuries. The change in the musical system in combination with the accepted ideals of the Romantic era determined the appearance of music by romantic composers. Improving of the piano mechanics and the keyboard system significantly expanded the range of expressive means and predetermined the further development of the piano playing technique. Teaching activities by F. Liszt and N.K. Medtner is associated with the development of the ideas of romanticism and the basic principles of the performing arts of romantics. Music teachers give special attention to an analysis of the pianistic apparatus, which is of great importance in improving the performing arts of playing the piano. Continuity of students in the sphere of basic principles of performing freedom determines the relevance of techniques based on key features of the pianist performing arts of romantics.